Persuasive Key Message Factors in Marjan Syrup Advertisements from 2021 - 2024 - Kezia Maureen; Jandy Luik; Astri Yogatama (Petra Christian University, 2024)
Marketing Public Relations (MPR) emphasises not on selling (as in advertising activities) but on providing information, education, and efforts to increase understanding through the addition of knowledge about a product brand. This approach has a stronger impact, and the message conveyed is more memorable to consumers. With a more intensive and comprehensive level of communication compared to advertising, MPR represents a higher concept than regular advertising. MPR emphasises the management aspect of marketing by highlighting consumer welfare. The Marjan Syrup advertisement is one of the most unique and interesting advertisements, which certainly does not escape the attention of the Indonesian public. Since 2019, Marjan has begun to step out of its